Direct measurement of the $$^{39}$$ 39 Ar half-life from 3.4 years of data with the DEAP-3600 detector - P. Adhikari; R. Ajaj; M. Alpízar-Venegas; P.-A. Amaudruz; J. Anstey; D. J. Auty; M. Batygov; B. Beltran; M. A. Bigentini; C. E. Bina; W. M. Bonivento; M. G. Boulay; et al. (European Physical Journal C: Particles and Fields)
Abstract The half-life of $$^{39}$$ 39 Ar is measured using the DEAP-3600 detector located 2 km underground at SNOLAB. Between 2016 and 2020, DEAP-3600 used a target mass of (3269 ± 24) kg of liquid argon distilled from the atmosphere in a direct-detection dark matter search. Such an argon mass also enables direct measurements of argon isotope properties. The decay of $$^{39}$$ 39 Ar in DEAP-3600 is the dominant source of triggers by two orders of magnitude, ensuring high statistics and making DEAP-3600 well-suited for measuring this isotope’s half-life. Use of the pulse-shape discrimination technique in DEAP-3600 allows powerful discrimination between nuclear recoils and electron recoils, resulting in the selection of a clean sample of $$^{39}$$ 39 Ar decays. Observing over a period of 3.4 years, the $$^{39}$$ 39 Ar half-life is measured to be $$(302 ± 8_stat ± 6_sys)$$ ( 302 ± 8 stat ± 6 sys ) years. This new direct measurement suggests that the half-life of $$^{39}$$ 39 Ar is significantly longer than the accepted value, with potential implications for measurements using this isotope’s half-life as input.